Hot carrier extraction in CH3NH3PbI3 unveiled by pump-push-probe spectroscopy - Lim, Swee Sien (2020)
Halide perovskites are promising materials for development in hot carrier (HC) solar cells, where the excess energy of above-bandgap photons is harvested before being wasted as heat to enhance device efficiency. Presently, HC separation and transfer processes at higher-energy states remain poorly understood. Here, we investigate the excited state dynamics in CH3NH3PbI3 using pump-push-probe spectroscopy. It has its intrinsic advantages for studying these dynamics over conventional transient spectroscopy, albeit complementary to one another. By exploiting the broad excited-state absorption characteristics, our findings reveal the transfer of HCs from these higher-energy states into bathophenanthroline (bphen), an energy selective organic acceptor far above perovskite's band edges. Complete HC extraction is realized only after overcoming the interfacial barrier formed at the heterojunction, estimated to be between 1.01 and 1.08 eV above bphen's lowest unoccupied molecular orbital level. The insights gained here are essential for the development of a new class of optoelectronics.